UMKM Melek Aturan: Pendampingan Intensif Legalitas Usaha UMKM di Desa Parseh Kecamatan Socah Kabupaten Bangkalan - Kurniyanto, Ifan Rizky; Destiarni, Resti Prastika; Zulkhaeriyah, Zulkhaeriyah; Arifiyanti, Nurul; Husna, Harir Mamluatul; Qoiroh, Shirotul Nur; Amalia, Lia; Rahmania, Handizah Kingkin; Saroh, Nisa May (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2025)
The community service aims to increase the understanding of business legalities such as NIB certificates, labels, and product packaging for SMEs in Parseh village, Socah district, and Bangkalan regency. The program implementation method is carried out in three stages: preparation, implementation, and post-implementation. The program focuses on two activities: assistance in issuing NIB certificates and knowledge about labels and product packaging to 30 MSMEs. These activities showed that most SMEs do not have NIB and lacked knowledge about the importance of business legality labels and packaging for three months. By conducting this program, all of the SMEs have succeeded in issuing NIB certificates, as well as successfully making mock-ups of labels and product packaging that are suitable for business improvement. The program evaluation shows that all aspects of the implementation of activities, such as benefits, facilities, and roles of the companions, have good values and relatively high NPS (Net Promoter Score) values, which are beneficial for SMEs.